Standardization of DPPH, ABTS and FRAP assays with six reference compounds for estimating antioxidant capacity of the tomato extracts using an ultrasound assisted extraction - Phitchan Sricharoen,; Suchila Techawongstein,; Devanand Luthria,; Saksit Chanthai, (International Journal of Phytomedicine, 2014)
Comparative calibrating of the antioxidant power of standard compounds, including gallic acid, catechin, Trolox, α-tocopherol, ascorbic acid and BHT were assessed by DPPH, ABTS and FRAP assays to determine total antioxidant activity of ten varieties of tomato extracts using ultrasound assisted extraction. Similar trends in their scavenging activities were found, resulted in the following rank; gallic acid > catechin > trolox > α-tocopherol > ascorbic acid > BHT. Both lipophilic and hydrophilic parts of the extracts were given in these assays in association with using hexane and 50% (v/v) methanol as their efficient extraction solvents, respectively. Their averaged values of the ascorbic acid equivalent antioxidant capacities (AEAC, µmol ascorbic acid/100g DW) were relatively confined in the same ranges of 1341.8-1834.5, 1334.2-2194.8 and 930.7-1734.7 for DPPH, ABTS and FRAP, respectively. In addition, both contents of total phenolics and ascorbic acid known as major deals of antioxidants were also determined, indicating highly existing constituents of the natural antioxidants.